Worldwide prevalence and burden of gastroparesis‐like symptoms as defined by the United European Gastroenterology (UEG) and European Society for Neurogastroenterology and Motility (ESNM) consensus on gastroparesis. Issue 8 (19th August 2022) - Huang, I‐Hsuan; Schol, Jolien; Khatun, Rutaba; Carbone, Florencia; Van den Houte, Karen; Colomier, Esther; Balsiger, Lukas Michaja; Törnblom, Hans; Vanuytsel, Tim; Sundelin, Elias; Simrén, Magnus; Palsson, Olafur S.; et al.
Abstract: Background/Objectives: The global epidemiology of gastroparesis is unknown. The European UEG and European Society for Neurogastroenterology and motility consensus defines Gastroparesis as a condition characterized by delayed gastric emptying in the absence of mechanical obstruction, with a symptom pattern of nausea and/or vomiting and overlapping postprandial distress syndrome (PDS). Real‐world evidence of this gastroparesis‐like symptom pattern is a crucial step in understanding the epidemiology of gastroparesis. Methods: In the Rome Foundation Global Epidemiology Study, 54, 127 respondents from 26 countries completed the Rome IV Diagnostic Questionnaire and variables associated with disorders of gut‐brain interaction via Internet. We selected subjects with gastroparesis‐like symptoms (GPLS) (nausea and/or vomiting ≥1 day/week and simultaneous PDS). Patients reporting organic gastrointestinal disease, or fulfilling criteria for self‐induced vomiting, cyclic vomiting or cannabinoid hyperemesis syndrome were excluded. We determined prevalence, associated comorbidities, quality of life (QoL) (PROMIS Global‐10), symptoms of anxiety and depression (PHQ‐4), somatic symptoms (PHQ‐12), and healthcare utilization. Results: The global prevalence of GPLS was 0.9% overall and 1.3% among diabetic individuals. Subjects with GPLS showed frequent overlapping of epigastric pain syndrome and irritable bowel syndrome. Subjects with GPLS had significantly lower body mass index, QoL, more non‐gastrointestinal somatic complaints, symptoms of anxiety and depression, higher medication usage and doctor visits in the overall and diabetic population, compared to subjects without these symptoms. Conclusions: GPLS are common worldwide and more common in diabetic patients. The symptom complex is associated with multiple aspects of illness and an increased healthcare consumption.